Retraction note: ANN-based MPPT algorithm for solar PMSM drive system fed by direct-connected PV array (Neural Computing and Applications, (2017), 28, 10, (3061-3072), 10.1007/s00521-016-2326-4) - Deniz, Erkan (Springer Science and Business Media Deutschland GmbH, 2024)
The Editor-in-Chief and the publisher have retracted this article. The article was submitted to be part of a guest-edited issue. An investigation by the publisher found a number of articles, including this one, with a number of concerns, including but not limited to compromised editorial handling and peer review process, inappropriate or irrelevant references or not being in scope of the journal or guest-edited issue. Based on the investigation's findings the Editor-in-Chief therefore no longer has confidence in the results and conclusions of this article. Erkan Deniz disagrees with this retraction. © The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature 2024.